Ipas Learning Based On Project-Based Learning With Ethnoscience Content On Waste Management To Improve Creative Thinking Skills - hizbullah, hizbullah; Anwar, Khairil; Ramadhan, M. Firman (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to develop a science learning design based on project based learning (PjBL) containing ethnoscience of waste processing and determine its effectiveness as an impact in improving students' creative thinking skills. The research method used is Research and Development (R&D), with a model (bord & gall) consisting of five stages, namely: needs analysis, learning design, learning development, field testing, and expert validation. Data collection techniques use observation, questionnaires and documentation. The sample of data sources is 15 fifth grade students of SDN 38 Mataram. Indicators of research success are seen from the results of validation by linguists, material experts, and media experts, while the effectiveness of learning is determined based on the results of the N-gain Test. The results of the study showed that validation carried out by linguists was 65% (good category), material experts 62% (good category), and media experts 63% (good category). Meanwhile, the results of the N-gain Test of students' creative thinking skills based on the fluent thinking indicator obtained an average of 56.55% (quite effective category), flexible thinking of 81.13% (effective category), original thinking of 65.21% (quite effective category), while the average value of the detailed thinking indicator was 57.62% (quite effective category), and the evaluating thinking indicator was 58.33% (quite effective category). Based on the results of theoretical and empirical studies, it was found that PjBL-based science learning containing ethnoscience of waste processing improves creative thinking skills.